2006
DOI: 10.1007/s10194-006-0324-0
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural evaluation in patients affected by chronic pain: a preliminary study

Abstract: The aim was to analyse the existing relation between a subjective evaluation of pain with the use of the Verbal Numerical Scale (VNS) and an objective behavioural measure associated with pain, by means of the Pain Behaviour Rating Scale (UAB). An observational correlation study was carried out in a hospital environment. The study included 61 patients affected with multiple forms of non-malignant chronic pain; the behaviour was observed by the nursing staff. In general, a positive but moderate correlation was o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
(26 reference statements)
0
6
0
Order By: Relevance
“…therapy: participants were evaluated while doing some type of therapy (eg, leg curls, music, behavioral therapy) [ 30 - 35 , 44 , 46 , 49 , 52 , 58 , 93 , 104 ].…”
Section: Resultsmentioning
confidence: 99%
“…therapy: participants were evaluated while doing some type of therapy (eg, leg curls, music, behavioral therapy) [ 30 - 35 , 44 , 46 , 49 , 52 , 58 , 93 , 104 ].…”
Section: Resultsmentioning
confidence: 99%
“…Finally, most of the data regarding pain in patients with dementia come from research using self-reporting of pain. Since the concordance between self-report and observation of pain has been demonstrated to be either low or moderate (Koho et al, 2001;Monina et al, 2006), it may be that the observation techniques used in this study cannot tap into the subjective experience of pain revealed by self-report.…”
Section: Prevalence Of Painmentioning
confidence: 91%
“…Pain has been defined as “an unpleasant sensory and emotional experience associated with actual or potential tissue damage or described in terms of such damage” [5]. This definition indicates that the perception of pain is a result of a complex interaction of physical, physiological, behavioural, and sociocultural factors [6, 7] and may be derived from the cognitive-emotional factors which influence the pain experience [6]. An individual's experience of pain may be outwardly expressed by demonstration of certain aberrant behaviours, with visible or audible responses indicative of discomfort or suffering such as grimacing and sighing [8, 9].…”
Section: Introductionmentioning
confidence: 99%